2011
DOI: 10.1186/1471-2229-11-92
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of Coffea arabica (L.) is greatly enhanced by using established embryogenic callus cultures

Abstract: BackgroundFollowing genome sequencing of crop plants, one of the main challenges today is determining the function of all the predicted genes. When gene validation approaches are used for woody species, the main obstacle is the low recovery rate of transgenic plants from elite or commercial cultivars. Embryogenic calli have frequently been the target tissue for transformation, but the difficulty in producing or maintaining embryogenic tissues is one of the main problems encountered in genetic transformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 74 publications
(100 reference statements)
5
63
0
3
Order By: Relevance
“…Application of the appropriate concentration of hygromycin B not only enabled effective selection of transformed cells but also allowed synchronization between selection and cell growth in different developmental growth phases, i.e. propagation and regeneration of the suspension cells, which usually involve different media combinations (Ribas et al 2011). …”
Section: Minimal Inhibitory Concentration Of Hygromycin B Against Boementioning
confidence: 99%
See 1 more Smart Citation
“…Application of the appropriate concentration of hygromycin B not only enabled effective selection of transformed cells but also allowed synchronization between selection and cell growth in different developmental growth phases, i.e. propagation and regeneration of the suspension cells, which usually involve different media combinations (Ribas et al 2011). …”
Section: Minimal Inhibitory Concentration Of Hygromycin B Against Boementioning
confidence: 99%
“…Agrobacterium-mediated transformation has been the most accessible tool with which to introduce heterologous DNA and manipulate gene expression in plants (Ribas et al 2011). Therefore, a reliable transformation and regeneration system with a low degree of chimerism and high regeneration frequency is a prerequisite (May et al 1995;Sági et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The experiment was replicated twice and each set within a replicate consisted of 45Á59 explants. Data were analyzed statistically and the confidence index was calculated as described by Ribas et al (2011). The early-mturing varieties with relatively small seeds, Huayu 20 and 26, presented the highest shoot regeneration percentage, with respective levels of 62.61 and 61.61% from cotyledon-derived explants, and 71.58 and 76.92% from mesocotyl-derived explants.…”
Section: Influence Of Genotype and Explant Source On Shoot Regeneratimentioning
confidence: 99%
“…For sonication for 3 and 5 min, the respective percentages of plant regeneration were 56.93 and 41.00%, and the respective transformation efficiencies were 5.45 and 3.50%. Statistical analysis revealed that submerging The confidence index was calculated as described by Ribas et al (2011). The confidence index was calculated as described by Ribas et al (2011).…”
Section: Effect Of Inoculation Treatment On Shoot Regeneration and Trmentioning
confidence: 99%
“…According RIBAS et al (2011), currently, embryogenic callus derived from leaf tissues is the most widely used target tissue for the genetic transformation of C. arabica and different callus stages can affect plant transformation. However, the induction of embryogenic tissues in C. arabica takes longer and is more diffi cult than in the others cultivated species.…”
Section: Introductionmentioning
confidence: 99%